Falsafah Hidup “Tallu Lolona A’pa’ Tauninna” Dalam Mewujudkan Ensiklik Laudato Si’ Art 137-162 Di Paroki Kristus Imam Agung Abadi Sangalla’ - Ma’dika, Meldayani; Krismiyanto, Alfonsus; Hatmoko, Tomas Lastari (Community Engagement and Emergence Journal (CEEJ), 2025)
The Tallu lolona a'pa' tauninna philosophy has long shaped the ecological awareness of the Torajan people. However, the influence of globalization and modernization has caused a shift in values that has eroded respect for these ecological principles. The Catholic Church, especially the Parish of Christ the Eternal Archpriest of Sangalla', needs to examine its role in reintegrating these noble values in order to awaken the ecological spirituality of the people as mandated in Laudato Si'. This research aims to describe the meaning and values of the Tallu lolona a'pa' tauninna philosophy of life, identify the values of the encyclical Laudato Si' integral ecology art 137-162 and analyze the relevance of the Laudato Si' encyclical in the implementation of the Tallu lolona a'pa' tauninna philosophy of life. This type of research is qualitative research, with an ethnographic approach. Data collection was carried out using interviews, observation and documentation methods. In-depth interviews were conducted with four informants. Observations are made at each data collection, as is documentation collected from relevant data. The data collected is then processed using an interactive analysis model as stated by Miles and Huberman. Data validity was carried out using triangulation techniques. The findings of this research reveal how the Toraja people's philosophy of life, Tallu lolona a'pa' tauninna, is manifested in the praxis of the encyclical Laudato Si' in Sangalla' Parish. The implementation of these values can be seen in the tradition of harvest thanksgiving which is held once a year after the harvest as a form of respect for nature and gratitude for God's grace. Apart from that, efforts to preserve the environment in Sangalla' Parish are also starting to be carried out in stages as a form of concern for preserving and protecting nature. This initiative is in line with the call in the encyclical Laudato Si' which emphasizes the importance of caring for the environment and paying attention to the sustainability of other living creatures, including pets.